Tanggungjawab Perdata Pemborong Akibat Kegagalan Bangunan dalam Perspektif Hukum Positif Indonesia - I ketut Suardika; I Nyoman Putu Budiartha; I Made puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
The collapse of several buildings as reported by various mass media including the collapse of the Yellow Bridge in Nusa Lembongan Klungkung, the perimeter of Soekarno Hatta Airport, the stock trading center building of the Indonesia Stock Exchange (IDX) is one of the problems faced today. For this incident, the Contractor who participated in the construction should be assumed to be responsible. The purpose of this research is to analyze the arrangement of building contract agreements in the perspective of Indonesian positive law and civil liability to contractors due to the occurrence of building failures in the perspective of Indonesian positive law. This research uses a normative legal research method with a statutory approach and a conceptual approach. Data collection techniques were collected through legal inventory. The sources used are primary and secondary sources of law. After the data is collected, then the data is analyzed systematically. The results of the research indicate that the collapse of the building outside the force majeure in UUJK 2/2017 is referred to as Building Failure. The Civil Code, UUJK 2/2017 concerning Construction Services and their derivative regulations are positive laws that still apply as legal umbrellas in regulating development implementation.